Analyzing Media Impact on Public Engagement with CSR Practices - Murniati Muhtar; Andi Subhan Amir; Sudirman Karnay (International Journal of Integrative Sciences, 2024)
This study examines the impact of media on public engagement with Corporate Social Responsibility (CSR) practices using a qualitative approach. The focus of the analysis is on the narratives formed by digital and traditional media and their influence on public perceptions of CSR activities. Data were gathered from content analysis of 100 news articles and 50 social media posts related to CSR activities of five multinational companies over the past year. The results indicate that consistently positive media narratives about CSR tend to enhance company reputation and public support, while negative exposure triggers less favorable public reactions. The study also found that influencers and digital activists play a crucial role in shaping online discourse about CSR, significantly influencing public perceptions. These findings suggest that companies need to design effective CSR communication strategies and continuously monitor and evaluate these strategies to ensure sustained positive impact on public engagement with CSR activities